Quenching accumulation of toxic galactose-1-phosphate as a system to select disruption of protein-protein interactions in vivo. (November 2004) - Gunde, Tea; Tanner, Stefan; Maur, Adrian Auf der; Petrascheck, Michael; Barberis, Alcide
The reverse two-hybrid system has been developed to readily identify molecules or mutations that can disrupt protein-protein interactions in vivo. This system is generally based on the interaction-dependent activation of a reporter gene, whose product inhibits the growth of the engineered yeast cell. Thus, disruption of the interaction between the hybrid proteins can be positively selected because, by reducing the expression of the negative marker gene, it allows cell growth. Although several counter-selectable marker genes are currently available, their application in the reverse two-hybrid system is generally confronted with technical and practical problems such as low selectivity and relatively complex experimental procedures. Thus, the characterization of more reliable and simple counter-selection assays for the reverse two-hybrid system continues to be of interest. We have developed a novel counter-selection assay based on the toxicity of intracellular galactose-1-phosphate, which accumulates upon expression of a galactokinase-encoding GAL1 reporter gene in the absence of transferase activity. Decreased GAL1 gene expression upon dissociation of interacting proteins causes reduction of intracellular galactose-1-phosphate concentrations, thus allowing cell growth under selective conditions.